Accelerated bridge construction projects using high performance concrete. (June 2020) - Akhnoukh, Amin K.
Abstract: The National Bridge Inventory (NBI) of the United States includes more than 600, 000 highway bridges. Approximately 25 % of the nation's inventory is structurally deficient or functionally obsolete. Currently, the Federal Highway Administration (FHWA) is investigating different alternatives to build new bridge with longer life-span, lower maintenance, and repair needs. Currently, the FHWA is successfully using accelerated bridge construction (ABC) techniques to expedite the construction of new bridges, and minimize material, labor, and equipment cost. In this research, the ABC of new bridges using prefabricated bridge elements and systems (PBES) is discussed, including the fabrication of precast/prestressed elements using an economic high performance concrete (HPC) mix, developed using local construction materials. The successful use of HPC in fabricating PBES used in ABC techniques allows the FHWA to construct new bridges under current budget restraints. This improves the overall rating of the bridge network within the United States.